Process quality monitoring at Altis Semiconductor - OTT, Holly (Institutional Knowledge at Singapore Management University, 2015)
Set in 2015, this case illustrates a typical process problem (or “excursion”) experienced in a production facility, considered from the perspective of the quality department. The case uses an example at Altis Semiconductor, where certain process parameters measured during production are indicating a problem. Patrick Béraud, the manager of the quality department at the silicon wafer fabrication plant in Corbeil-Essonnes, France, is to lead the investigation, including problem identification, problem containment, root cause analysis and management reporting. This case applies standard quality concepts, including statistical process control, yield analysis and data correlation. This case is designed for operations or industrial engineering students at the undergraduate or graduate levels in order to illustrate the use of standard quality concepts in a real setting, including process monitoring, data analysis and risk analysis. This case also exercises systematic problem solving and, and therefore can be useful for a graduate level project management class (for example, in an MBA or EMBA programme). It is not necessary to have a deep understanding of the process details, but the situation is specific enough that the students must spend some time to think about the problem, rather than to blindly apply formulas. Students should be able to fulfill the following learning objectives: 1) Evaluate a complex quality problem in a production setting and plan the response, 2) Perform a root cause analysis using data correlation, 3) Estimate the expected financial impact of the production problem using parameter Upper and Lower Specification Limits (USL/LSL), 4) Summarise the situation and recommend action items to upper management/customers, and 5) Explain the “8 Disciplines” process for approaching and solving quality problems and communicating to the customer.